2019
DOI: 10.2172/1524048
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Geothermal Power Generation utilizing Geologic Thermal Energy Storage (Final Seedling Project Report)

Abstract: This report concludes that there is a cost-effective strategy for seasonal storage of heat that will provide firm, but dispatchable, electrical generating capacity in times when other renewable energy is not available to meet demand. Deployment of the technology appears to require no new technology, but instead combines solar, geothermal, and conventional oil and gas drilling technologies in a novel way. The study basis is the use of sedimentary geologic formations as a medium for thermal energy storage (TES),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…This system uses concentrating solar power to produce hot water that is injected into an aquifer, creating a synthetic geothermal reservoir. The geothermal heat stored in the subsurface can then be dispatched when needed (Wendt et al 2019, Sharan et al 2020. Other technologies, such as geothermal battery energy storage systems, are currently under development, but studies suggest that nearly all of the stored heat can be practically recovered in these types of systems (Green et al 2020).…”
Section: Photo From Istockphoto 465436017mentioning
confidence: 99%
“…This system uses concentrating solar power to produce hot water that is injected into an aquifer, creating a synthetic geothermal reservoir. The geothermal heat stored in the subsurface can then be dispatched when needed (Wendt et al 2019, Sharan et al 2020. Other technologies, such as geothermal battery energy storage systems, are currently under development, but studies suggest that nearly all of the stored heat can be practically recovered in these types of systems (Green et al 2020).…”
Section: Photo From Istockphoto 465436017mentioning
confidence: 99%
“…The NSF funded SedHeat Geothermal Energy Project [4,5] recommended injecting hot water derived from solar thermal energy into low-quality geothermal sedimentary basins. Recently, a team led by Idaho National Laboratory [6] showed that high permeability and porosity formations could potentially provide storage for solar heated water, with subsequent cyclic production and reinjection. Only a few studies consider anisotropy in a geothermal reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Geothermal subsurface settings are used directly for recreation, for indirect uses such as heating and certainly for generating electricity. It is proposed that surrogate geothermal reservoirs can also be engineering and used as a medium for storing hot water that is heated at a surface facility using excess electricity or direct solar heat (Wendt et al, 2019a(Wendt et al, , 2019b. This stored water can be produced back and converted to electricity on demand.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors that control the functionality of such a system in a homogeneous reservoir have been addressed elsewhere (Wendt et al, 2019a(Wendt et al, , 2019bGreen et al, 2020;Panja et al, 2020. However, heterogeneity or geostatistical distribution of geologic parameters such as permeability has been shown to have a major impact on the fluid flow in porous media.…”
Section: Introductionmentioning
confidence: 99%